Thai Seven Year Old Early Learner Creativity Design and Study Activities Promotion - Suthasini Bureekhampun; Kittikorn Techakarnjanakij; Piya Supavarasuwat (My University, 2021)
The objectives of the research were to investigate a creative learning promotion activity package for 30 Thai seven-year-old, first-grade school students.Secondly, to design a creative learning promotion activity package, followed by an assessment of the creative learning development process from a series of creative learning promotion activities, and finally, to study the level of parental satisfaction from the final model's related student activities.Additional analysis was undertaken by a group of three child behavioral and learning development experts, and three design experts using a specific selection method.The sample consisted of 30 primary school seven-year-old early learners and 30 parents who were selected by the use of the quota selection method and purposive sampling.The research instruments used included interview forms, product model evaluation questionnaires, behavioral observation forms, and parent satisfaction questionnaires.The results of the research showed that thinking development (TD), physical development (PD), emotional development (ED), and social development (SD) on creativity were affected by a broad spectrum of factors.These included the child's understanding of their surroundings, the use of fine hand muscles, their ability to perform more complex activities, their cheerfulness, social activity, and peer activities, and their ability to concentrate on activities for longer periods.One instrument used for the study included the analysis of five-game board formats used for the development in TD, PD, ED, and SD.The results of the evaluation from the study's product experts determined that style model 3 (Magician's Castle set) was very suitable.
Keywords: Promotion (chess); Creativity in Education and Neuroscience